Pengaruh Penggunaan Media Botol Cerdas terhadap Hasil Belajar Bahasa Indonesia Siswa di MIN 10 Medan - Nadya Zain Ritonga; Salminawati Salminawati; Riris Nurkholidah Rambe (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to determine the effect of using smart bottle media to improve the learning outcomes of Indonesian students in grade IV at MIN 10 Medan, which consist of two classes. The researcher took class IV-A and IV-B to be used as a sample, totaling 12 people as the experimental class and 12 people as the control class. This type of research is a quantitative experimental research (Quasi Experimental Design) with the Nonequevalent Control Group Design approach. Data collection techniques with observation, documentation, and test. Based on data analysis from research result werw obtained: 1) The Indonesian language learning result of students at MIN 10 Medan using picture story can be seen from the average final test (posttest) score in the control class, namely class IV-A, which obtained an average score of 48,33 and a standar deviation of 15,27. 3) The Indonesian language learning results of students at MIN 10 Medan using a smart bottle media can be seen from the average final test (posttest) score in the experimental class, namely class IV-B, which obtained an average score of 53,33 and a standard deviation of 16,69. 3) The process of implementing smart bottle media in Indonesian language subjects in class IV MIN 10 Medan is going well and can improve student learning outcome in Indonesian language subjects. This can be seen from comparison of learning outcomes between the experimental class and the control class, where the learning outcomes of students in the experimental class are higher than the learning outcomes of students in the control class.